Social Media for Social Good or Evil: An Introduction. (July 2018) - Hemsley, Jeff; Jacobson, Jenna; Gruzd, Anatoliy; Mai, Philip
In the heyday of social media, individuals around the world held high hopes for the democratizing force of social media; however, in light of the recent public outcry of privacy violations, fake news, and Russian troll farms, much of optimism toward social media has waned in favor of skepticism, fear, and outrage. This special issue critically explores the question, "Is social media for good or evil?" While good and evil are both moral terms, the research addresses whether the benefits of using social media in society outweigh the drawbacks. To help conceptualize this topic, we examine some of the benefits (good) and drawbacks (evil) of using social media as discussed in eight papers from the 2017 International Conference on Social Media and Society. This thematic collection reflects a broad range of topics, using diverse methods, from authors around the world and highlights different ways that social media is used for good, or evil, or both. We conclude that the determination of good and evil depends on where you stand, but as researchers, we need to go a step further to understand who it is good for and who it might hurt.